Systematic end-to-end testing of multiple target treatments using the modular RUBY phantom. (9th December 2021) - Brodbek, Leonie; Kretschmer, Jana; Büsing, Katrin; Looe, Hui Khee; Poppe, Björn; Poppinga, Daniela
Abstract: The RUBY head phantom in combination with the System QA insert MultiMet can be used for simultaneous point dose measurements at an isocentric and two off-axis positions. This study investigates the suitability of the system for systematic integral end-to-end testing of single-isocenter multiple target stereotactic treatments. Several volumetric modulated arc therapy plans were optimized on a planning CT of the phantom positioned in a stereotactic mask on the stereotactic treatment board. The plans were created for three artificial spherical target volumes centred around the measurement positions in the MultiMet insert. Target diameters between 5 and 40 mm were investigated. Coplanar and non-coplanar plans were optimized using the collapsed cone algorithm of the Oncentra Masterplan treatment planning system and recalculated with the Monte Carlo algorithm of the Monaco treatment planning system. Measurements were performed at an Elekta Synergy linear accelerator. The head phantom was positioned according to clinical workflow comprising immobilization and CBCT imaging. Simultaneous point dose measurements at all target positions were performed with three PinPoint 3D chambers (type 31022) as well as three microDiamond detectors (type 60019) and compared to the treatment planning system calculations. Furthermore, the angular dependence of the detector response was investigated to estimate the associated impact on the measured point dose values. Considering all investigated plans, PTV diameters and positions, the point doses calculated with the Monaco treatment planning system and the microDiamond measurements differed within 3.5%, whereas the PinPoint 3D showed differences of up to 6.9%. Point dose differences determined in comparison to the Oncentra Masterplan dose calculations were larger. The RUBY system was shown to be suitable for end-to-end testing of complex treatment scenarios such as single-isocenter multiple target plans.